Organised Crime Control Policy: Case Study of Turkey - Bulatović, Aleksandra (Zbornik Instituta za kriminološka i sociološka istraživanja, 2010)
The author of the paper discusses the main elements of Turkish legislation and institutional policy to address organised crime against the backdrop of the good practice (good governance) scheme prevalent adopted in the European Union EU. She argues that Turkish institutions need to progress towards a complete policy transformation vis-á-vis organised crime, which would then also open up avenues for a more comprehensive political progress within the EU candidature. Turkey is a transitional country, geographically located in a region that is affected by the typical problems relating to weak states, including organised crime. Thus, this is a country that faces numerous difficulties that stifle the already initiated reform processes. Turkey’s European Union member candidature means that Turkey is obliged to institute an effective anti-organised crime strategy, and the Turkish authorities have undertaken an array of internal and external measures to reach the standards in crime prevention.